Draw cars - DuBosque, Doug (Columbus, NC Peel Productions, Inc., 1998)
Provides step-by-step instructions for drawing popular cars, including racing cars, exotics, and off-road vehicles
Keywords: Automobiles in art; Drawing--technique; Juvenile works